My tractor, your tractor - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The principle behind farm machinery cooperatives is that farmers club together to share the cost of buying and maintaining a tractor, trailer or threshing machine...